RE: The value of testicular ultrasound in the prediction of the type and size of testicular tumors - Kamarulzaman, Mohd Nazli; Che Mohamed, Siti Kamariah (Brazilian Society of Urology, 2016)
We read with great interest the article “The value of testicular ultrasound in the prediction of the type and size of testicular tumors” by Shtricker A. et al (1). This article highlights an interesting role of testicular ultrasound finding in managing testicular tumor, particularly regarding the ability of testicular ultrasound to differentiate between these three lesions: benign lesion, seminomatous germ cell tumor (SGCT) and non-seminomatous germ tumor (NSGCT). The presence of necrosis is more suggestive of malignant tumors, whereas hypoechogeneity and fibrosis on testicular ultrasound are more suggestive of SGCT type (1). These finding will increase the ability to differentiate type of testicular tumor preoperatively in addition to traditionally use tumor markers. Hopefully in near future the characteristic of different type of cancers can be done to form risk stratification Table. On the other hand, this article gives us a big doubt regarding the ability of preoperative ultrasound to estimate the tumor size as compared to pathological measurement. It was not verified the actual time interval between diagnostic ultrasound and the orchiectomy. Fast growing cancer will give significant change in size within short period of time. Thus, the ultrasound findings will be smaller in comparison to pathological size if the time interval between the ultrasound and operation was a week or more. In contrast to malignant lesion, the benign lesion was well documented as slow growing and expected to have similar size during diagnostic ultrasound and pathological specimen regardless the time interval; as shown in this study that 100% of benign tumors showed similar sizes for both measurements (1, 2). Furthermore, the study was conducted in multicentre which will give more varieties in term of technique as ultrasound requires a highly experienced and skilled operator, as well as advance equipment (3).